2020
DOI: 10.1021/acs.jpca.9b11275
|View full text |Cite
|
Sign up to set email alerts
|

Microsolvation in V+(H2O)n Clusters Studied with Selected-Ion Infrared Spectroscopy

Abstract: Gas-phase ion–molecule clusters of the form V+(H2O) n (n = 1–30) are produced by laser vaporization in a supersonic expansion. These ions are analyzed and mass-selected with a time-of-flight mass spectrometer and investigated with infrared laser photodissociation spectroscopy. The small clusters (n ≤ 7) are studied with argon tagging, while the larger clusters are studied via the elimination of water molecules. The vibrational spectra for the small clusters include only free O–H stretching vibrations, while l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 124 publications
5
25
2
Order By: Relevance
“…The measured photodissociation cross sections for n = 1-4 are shown in Figure 1. As shown in previous studies, 33,35,41 35,41 For n = 3, the T-shaped isomer reported by Ohashi and coworkers 35 is within error limits isoenergetic with the Y-shaped structure from Figure 1, and exhibits a small imaginary frequency in our calculations. This indicates that the position of the oxygen atoms is not very well defined for this cluster size and that the water molecules undergo large-amplitude motions even at low temperatures in the coordination plane of the metal center for n = 3.…”
Section: Photodissociation Of V + (H 2 O) 1-4supporting
confidence: 90%
See 2 more Smart Citations
“…The measured photodissociation cross sections for n = 1-4 are shown in Figure 1. As shown in previous studies, 33,35,41 35,41 For n = 3, the T-shaped isomer reported by Ohashi and coworkers 35 is within error limits isoenergetic with the Y-shaped structure from Figure 1, and exhibits a small imaginary frequency in our calculations. This indicates that the position of the oxygen atoms is not very well defined for this cluster size and that the water molecules undergo large-amplitude motions even at low temperatures in the coordination plane of the metal center for n = 3.…”
Section: Photodissociation Of V + (H 2 O) 1-4supporting
confidence: 90%
“…This observation is in line with earlier infrared spectroscopy that the first solvation shell is fully occupied with four water molecules. 35,41 Further hydration in the second solvation shell does not significantly affect the electronic structure of the V + ion in the core and mostly broadens the bands.…”
Section: Photodissociation Of V + (H 2 O) 5-20mentioning
confidence: 99%
See 1 more Smart Citation
“…72 The most red-shifted band is also present for clusters n 4 4, centred at 3220 cm À1 for n = 7, and even in the largest cluster with n = 35, a slightly blue-shifted maximum at 3230 cm À1 can be identified in an overall broad absorption band that is typical for water clusters. The shift to the red, as outlined in many previous publications, 3,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][73][74][75] is due to the metal-induced polarisation on the water molecules, which removes electron density from bonding orbitals on the O-H bond, causing an observed red-shift. As discussed previously for Zn + (H 2 O) n complexes, 43 the polarizing effect of Zn + , when compared to other singly-charged metal ions, 3,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][73][74]…”
Section: Resultsmentioning
confidence: 83%
“…Our group has an extended history in studying these systems [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Infrared action spectroscopy, coupled with quantum chemical calculations, is a powerful technique used to investigate the structures of gas-phase molecular complexes, [52][53][54][55][56][57][58][59][60] in particular hydrated metal ions [61][62][63][64][65][66][67][68][69]. We recently published a study investigating hydrated zinc monomer ions Zn + (H 2 O) n with up to 35 water molecules, [70] where we found evidence for surface solvation of Zn + , which was previously established by Duncan and co-workers for n ≤ 4 [71].…”
Section: Introductionmentioning
confidence: 99%